Factors Determining the Efficacy of Guided Intervention-based Management of Shoulder Adhesive Capsulitis Secondary to Breast Cancer Treatment: A Prospective Study - Chandrakant Pilania; Himanshu Agrawal; Pravin Mahadeorao Pisudde; Bhavay Sonik; Ravi Gaur (Indian Journal of Physical Medicine & Rehabilitation)
Background: This prospective study aimed to determine the factors influencing the efficacy of guided intervention-based management of shoulder adhesive capsulitis secondary to breast cancer treatment. Adhesive capsulitis presents a significant challenge in breast cancer survivors, impacting their quality of life and shoulder functionality. Materials and Methods: The patients exhibiting adhesive capsulitis subsequent to ipsilateral breast cancer treatment were included in the study. Diagnostic confirmation involved clinical assessment, utilising criteria including pain levels and restriction of joint range of motion. Guided interventions consisted of suprascapular nerve blocks and glenohumeral joint hydrodilatation under ultrasound guidance, followed by Bach’s rehabilitation protocol. Patient characteristics and breast cancer treatment details were considered as exposure variables. Statistical analysis involved descriptive statistics, χ2 tests, Fisher’s exact tests and multivariate logistic regression. Results: The results revealed that body mass index, comorbidities (hypertension and diabetes), hormone receptor status and radiation therapy significantly impacted treatment outcomes. Shoulder assessment metrics, such as flexion, extension and rotation, showed promising predictive value for treatment success. The study highlighted the importance of tailoring treatment based on both patient-specific factors and shoulder assessment metrics for effective management of adhesive capsulitis in breast cancer survivors. Conclusions: The study’s outcomes indicate the effectiveness of guided interventions in managing shoulder adhesive capsulitis in breast cancer survivors, emphasising the significance of personalised treatment approaches. The research sheds light on the impact of patient-specific factors and cancer treatment details on the success of management strategies. In addition, the study underscores the value of shoulder assessment metrics in predicting treatment outcomes, highlighting the need for tailored and comprehensive treatment for this specific patient population.